BLOCK CHAIN: THE PROSPECT OF ARTIFICIAL INTERNET. - WISETSRI, WORAKAMOL; MAKKAR, SANDHYA; KUMAR, SANTOSH; GUPTA, SHASHI KANT (Turkish Journal of Physiotherapy Rehabilitation, 2021)
During the year 2017, Block chain became a buzzword and its erroneous usage, created a misleading image mostly due to the misinformation and unawareness of the society regarding this new technology. As Block chain is a rather recent topic, the majority of the data and information for this study was collected through hours of extensive research online. Despite the fact of a high abundance of online resources, the information gathered needed to be cross-checked with other resources as part of the information were incorrect. For the technical side of this study, books related to programming in Solidity language and online tutorials were explored as well. The codes available in this study were programmed to demonstrate the technicalities of Blockchain in a simplistic way. The study shows that Block chain has indeed potential to become an important aspect of our lives by reinforcing data security and by giving more power to the society. Throughout the study only the main aspects and feature of Block chain were analysed.